Perinatal undernourishment provokes long-lasting alterations of clusterin and fumarate hydratase expression in the rat nucleus accumbens. (2nd September 2022) - Rodríguez-Rivera, Carmen; González-Martín, Carmen; Fernández-Millán, Elisa; Álvarez, Carmen; Escrivá, Fernando; Alguacil, Luis F.
ABSTRACT: Background: Background: Perinatal malnutrition seems to provoke important neurochemical alterations in the brain that lead to higher vulnerability to develop neuropsychiatric disorders in the adulthood. Objectives: We have examined the persistence and reversibility of the changes induced by perinatal undernourishment on the expression of fumarate hydratase in the rat nucleus accumbens, bearing in mind that this expression has been previously linked with addictive disorders. Clusterin, a multifunctional protein known to be neuroprotective and possibly related to addiction in humans, was studied in parallel. Methods: Female Wistar rats underwent a severe restriction of food during gestation and lactation. Upon weaning, a subgroup of undernourished animals was switched to normal chow and another one continued under food restriction. Control rats and their mothers were fed on chow along the experiment. Fumarate hydratase and clusterin were quantified by western blot after five months of postnatal life in the three experimental groups. Results: Food restriction along the whole experimental period provoked a marked upregulation of both clusterin and fumarate hydratase in the mitochondrial fraction of the nucleus accumbens. In the case of clusterin, this upregulation was also observed in the cytosolic fraction of the nucleus accumbens. When undernourishment was limited to gestation and lactation the two proteins appeared downregulated with respect to controls. Conclusion: The results are consistent with the idea that perinatal malnutrition provokes marked changes in brain neurochemistry that are not fully corrected by the rehabilitation of normal feeding and could be linked to behavioural disturbances in the adulthood, that is, increased vulnerability to addiction.